Dynamics of the value orientations of students – future coaches in the process of professional training - Flotskaya, N.Yu.; Bulanova, S.Yu.; Ponomareva, M.A.; Zavarin, A.N. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to study the dynamics of the structure of value orientations among students – future coaches at the initial and final stages of professional education. Methods and structure of the study. The respondents of the study were students – future coaches of the first and senior years, studying at the Federal State Autonomous Educational Institution of Higher Education “Northern (Arctic) Federal University named after M.V. Lomonosov.” To study the value orientations of students – future coaches, the method “Free Choice of Values” (E.B. Fantalova) was applied, which makes it possible to assess various life values by the criteria of importance (how significant the value is) and attainability. The factor structure of the value orientations was determined using factor analysis (method: Varimax) with Kaiser normalization. Results and conclusions. The conducted study made it possible to identify significant changes in the factor structure of the value orientations among students – future coaches from the initial to the final stage of professional education. It was established that at the initial stage of professional education the factor “Importance of life values” dominates, whereas at the final stage of professional education the factor “Attainability of life values” comes to the fore, which may testify to the transition from an idealistic perception of life values to a realistic assessment of the possibilities of their attainability. Changes also occur in the content of the factors themselves: a shift of value orientations from individual-hedonistic to socially significant and professional ones by the end of professional education. The obtained results can be used for the psychological-pedagogical support of the preparation of future coaches and the improvement of the system of their professional education.